Odpowiedzi

2009-10-11T14:16:50+02:00
A) (√5-√3)²-(√5+√3)²=5-2√15+3-5-2√15-3=-4√15
b)(√3-2)³-(√3+2)²=3-4√3+4-3-4√3-4=-8√3
c)(2x-1)²-(x-2)²=4x^2-2x+1-x^2+4x-4=3x^2+2x-3
d)(x+2)²-3(x+1)(x-7)=x^2+4x+5-3x^2+21x-3x+21=-2x^2+22x+25

^ do potęgi
  • Użytkownik Zadane
2009-10-11T14:17:18+02:00
A) (√5-√3)²-(√5+√3)²=((√5)²-2*√5*√3+(√3)²)-((√5)²+2*√5*√3+(√3)²)=(5-2√15+3)-(5+2√15+3)=(8-2√15)-(8+√15)=8-2√15-8-2√15=-4√15
b)(√3-2)³-(√3+2)²=((√3)²-2*2*√3+2²)-((√3)²+2*3*√3+2²)=(3-4√3+4)-(3+4√3+4)=(7-4√3)-(7+4√3)=7-4√3-7-4√3=-8√3
c)(2x-1)²-(x-2)²=((2x)²-2*2x*1+1²)-(x²-2*2*x+2²)=(4x²-4x+1)-(x²-4x+4)=4x²-4x+1-x²+4x-4=3x²-3
d)(x+2)²-3(x+1)(x-7)=(x²+2*2*x+2²)-3(x²-7x+x-7)=(x²+4x+4)-3(x²-6x-7)=x²+4x+4-3x²+18x+21=-2x²+22x+25
2009-10-11T14:33:52+02:00
(a+b)²=a²+2ab+b²
(a-b)²=a²-2ab+b²
(a-b)(a+b)=a²-b²


a) (√5-√3)²-(√5+√3)²=5-2√15+3-5-2√15-3=-4√15
b)(√3-2)³-(√3+2)²=3-4√3+4-3-4√3-4=-8√3
c)(2x-1)²-(x-2)²=4x²-4x+1-x²+4x-4=3x²-3
d)(x+2)²-3(x+1)(x-7)=x²+4x+5-3x²+21x-3x+21=-2x²+22x+25